Anti-integrin αvβ6 antibody in Takayasu arteritis patients with or without ulcerative colitis - Ishikawa, Yuki; Yoshida, Hiroyuki; Yoshifuji, Hajime; Ohmura, Koichiro; Origuchi, Tomoki; Ishii, Tomonori; Mimori, Tsuneyo; Morinobu, Akio; Shiokawa, Masahiro; Terao, Chikashi (Frontiers in Immunology, 2024)
Background: It has been well documented that Takayasu arteritis (TAK) and ulcerative colitis (UC) coexist in the same patients. HLA-B*52 characterizes the co-occurrence, which is one of the common genetic features between these two diseases, indicating shared underlying pathologic mechanisms. Anti-integrin αvβ6 antibody (Ab) is present in sera of UC patients in a highly specific manner. We investigated if there were any associations between anti-integrin αvβ6 Ab and TAK, considering the risk HLA alleles. Methods: A total of 227 Japanese TAK patients were recruited in the current study and their serum samples were subjected to measurement of anti-integrin αvβ6 Ab by ELISA. The clinical information, including the co-occurrence of UC, was collected. The HLA allele carrier status was determined by Luminex or genotype imputation.The information about the presence of UC was available for 165 patients, among which eight (4.84%) patients had UC. Anti-integrin αvβ6 antibody was identified in 7 out of 8 TAK subjects with UC (87.5%) while only 5 out of 157 (3.18%) TAK subjects without UC had the antibody (OR 121, p=7.46´10 -8 ). A total of 99 out of 218 (45.4%) patients were HLA-B*52 carriers. There was no significant association between the presence of anti-integrin αvβ6 Ab and HLA-B*52 carrier status in those without UC (OR 2.01, 95% CI 0.33-12.4, p = 0.189).The prevalence of anti-integrin αvβ6 Ab was high in TAK patients with UC, but not in the absence of concomitant UC. The effect of HLA-B*52 on anti-integrin αvβ6 Ab production would be minimal.